The Influence of Endorser Credibility and Swift Guanxi on Consumer Purchase Intention in TikTok Live Streaming: The Mediating Role of Trust - Richard Nesimnasi; Felix Hugo Waworuntu; Stefanus Budy Widjaja Subali; Adhika Putra Wicaksono (Journal of Social Commerce, 2026)
This study analyzes the influence of endorser credibility and swift guanxi on consumer purchase intentions within TikTok live streaming while evaluating trust as a mediating variable. The research employs a quantitative approach utilizing a survey method to collect data from 110 active TikTok users who have completed purchases through live broadcasts. Data analysis was conducted using Partial Least Squares Structural Equation Modeling with the assistance of SmartPLS software. The empirical results reveal that endorser credibility has a positive and significant effect on both purchase intention and consumer trust. Swift guanxi also positively and significantly impacts purchase intention and trust although it exhibits a lower overall influence compared to endorser credibility. Crucially the analysis proves that trust successfully mediates the relationship between endorser credibility and purchase intention but completely fails to mediate the relationship between swift guanxi and purchase intention. These findings highlight a major theoretical divergence indicating that while traditional credibility relies on cognitive trust, the emotional immediacy of swift guanxi bypasses traditional risk assessments to drive spontaneous purchases directly.